FORMULASI DAN UJI EVALUASI SEDIAAN LIP BALM KOMBINASI EKSTRAK ETANOL DAGING LIDAH BUAYA (Aloe vera) DAN DAGING BUAH ALPUKAT (Persea americana Mill) SEBAGAI PELEMBAB BIBIR - Masruroh, Sururul Kamalin; Wardani, Tatiana Siska; Listyani, Tiara Ajeng (JIFI (Jurnal Ilmiah Farmasi Imelda), 2025)
The lips are sensitive and prone to dryness and chapping, requiring special care. This study aimed to develop a Lip Balm preparation that meets physical quality standards and to determine its activity as a lip moisturizer. It also determined the optimal concentration for a Lip Balm formulation using a combination of 70% ethanol extract of Aloe vera and avocado (Persea americana Mill.) pulp. Aloe vera contains lignin, and avocado contains vitamins A, C, and E, which are essential for skin health. This study was conducted experimentally using five formula variations: F0 (0%), F1 (10%), F2 (15%), F3 (20%), and a positive control (Vaseline Repairing Jelly). Physical quality evaluation included organoleptic testing, homogeneity, pH, spreadability, adhesion, spreadability, moisture testing, irritation testing, hedonic testing, and stability testing. The results showed that all formulas had a semi-solid texture and color, varying depending on the extract concentration, were homogeneous, had a pH within the safe range (4.5-6.5), and met physical quality requirements. Moisture testing showed an increase in lip moisture levels after 14 days of use, with formula F3 providing the best moisturizing effect. In conclusion, the combination of Aloe vera and avocado (Persea americana Mill) extracts can be formulated into an effective Lip Balm as a natural lip moisturizer, with the best concentration in formula F3, with a moisture value of 47.3%.